2011
DOI: 10.1560/ijee.57.1-2.23
|View full text |Cite
|
Sign up to set email alerts
|

Plant community dynamics in shortgrass steppe with grazing relaxation and imposition by large and small herbivores

Abstract: Semiarid rangelands often respond slowly to rest/relaxation of grazing pressure by large herbivores, and the effects of grazing are most often inferred from this direction of study because the imposition of grazing onto previous ungrazed/lightly grazed areas occurred prior to the age of scientific studies. These rangelands host a diversity of small and large herbivores, but grazing studies most often concern effects of the large generalists. Here, the effects of herbivore body size on plant species richness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
1
15
1
Order By: Relevance
“…Several studies in other rangelands have also observed grazing-related changes that are reversible, but only over relatively long (e.g. decadal) time-scales (Fuhlendorf, Briske & Smeins 2001;Valone et al 2002;Milchunas 2011).…”
Section: E V I D E N C E F O R a L T E R N A T I V E S T A B L E S T mentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies in other rangelands have also observed grazing-related changes that are reversible, but only over relatively long (e.g. decadal) time-scales (Fuhlendorf, Briske & Smeins 2001;Valone et al 2002;Milchunas 2011).…”
Section: E V I D E N C E F O R a L T E R N A T I V E S T A B L E S T mentioning
confidence: 99%
“…However, studies from several different rangelands have emphasized that grazing‐induced vegetation changes can occur gradually over time‐scales of decades or longer, and are frequently reversible at those time‐scales (Fuhlendorf, Briske & Smeins ; Valone et al . ; Milchunas ; Bestelmeyer et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on data collected during the International Biological Program (IBP), their biomass consumption per unit area is relatively low, estimated to be ˜3% of aboveground net primary production (ANPP) compared with ˜40% by large herbivores at moderate cattle grazing intensity (Lauenroth and Milchunas 1991). Short‐term exclusion of large‐plus‐small herbivores resulted in greater richness of rare species than even long‐term exclusion of only large herbivores, indicating that selective consumers of a small proportion of ANPP might promote faster and greater effects on plant diversity than a generalist that consumes a much higher proportion (Bakker et al 2006, Milchunas 2011). Based on only two early years of data, effects of small herbivores on species richness observed in a very wet year were generally not evident in the following drought year with low ANPP, when drought‐ and grazing‐tolerant species predominated in all treatments (Milchunas 2011).…”
mentioning
confidence: 99%